2020
DOI: 10.1155/2020/8691757
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Nodulation, and Yield Responses of Groundnut (Arachis hypogaea L.) as Influenced by Combined Application of Rhizobium Inoculant and Phosphorus in the Guinea Savanna Zone of Ghana

Abstract: Groundnut yields obtained by farmers in northern Ghana are generally low due to low soil fertility resulting from continuous cropping coupled with low use of external inputs. There is therefore the need to use systems’ internal resources such as biological nitrogen fixation efficiently to enhance crop production. This on-station experiment investigated nodulation and pod yield responses of three groundnut varieties, namely Obolo, Oboshie and Samnut 22 to inoculation with rhizobium inoculants of exotic strains,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 9 publications
(5 reference statements)
4
22
0
3
Order By: Relevance
“…The favorable soil structure under polythene mulch also improved the soil total porosity, capillary porosity and aeration porosity, which in turn may have improved pegging and pod formation in the soil [42]. Similar results, including higher pod dry weights, improved peg to pod conversion and shelling percentages were also reported under seed inoculated with Rh than under noninoculated peanut seed [43,44].…”
Section: Yield Attribution Characteristicssupporting
confidence: 66%
“…The favorable soil structure under polythene mulch also improved the soil total porosity, capillary porosity and aeration porosity, which in turn may have improved pegging and pod formation in the soil [42]. Similar results, including higher pod dry weights, improved peg to pod conversion and shelling percentages were also reported under seed inoculated with Rh than under noninoculated peanut seed [43,44].…”
Section: Yield Attribution Characteristicssupporting
confidence: 66%
“…Similarly, Boddey et al (2017) reported a higher nodule number in Northern Ghana due to the application of the Bradyrhizobium inoculant with P fertilizer. The study of Asante et al (2020) on yield response of groundnut to inoculation and P application also supports this conclusion. In the on-station experiment, nodule and effective nodule formation did not differ significantly among IR, PR, and V interactions.…”
Section: Growth Yield and Yield Componentssupporting
confidence: 67%
“…Therefore, P deficiency can negatively affect access to atmospheric N by legumes (Adjei-Nsiah et al, 2018). In confirming this, Asante et al (2020) indicated that rhizobium activity and N2 fixation are negatively affected when the system lacks phosphorus (P) since P serves as an energy source for the rhizobia. Similarly, the requirement of P in nodulating legumes is higher compared to non-nodulating crops as it contributes significantly to root development (Tang et al, 2001), root nodulation (Nwaga and Ngo Nkot, 1998), and shoot uptake of N, P, and K (Ramesh et al, 1997) in legumes.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This could be due to the availability of more nutrients to the microbes due to weed free condition. [1] . The study of Effiong et al, 2019) [4] showed that inoculation of fungi Glomus clarum contributes towards higher pod yield in groundnut.…”
Section: Resultsmentioning
confidence: 99%